The Historical Emergence of Quantity Theory - Dempsey, Bernard W. (Quarterly Journal of Economics, 1935)
Journal Article The Historical Emergence of Quantity Theory Get access Bernard W. Dempsey, S. J. Bernard W. Dempsey, S. J. St. Louis University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 50, Issue 1, November 1935, Pages 174–184, https://doi.org/10.2307/1882348 Published: 01 November 1935